Chemotaxis of T-cells after infection of human choroid plexus papilloma cells with Echovirus 30 in an in vitro model of the blood-cerebrospinal fluid barrier - Rudolph, Henriette; Weber, Claudia Ellen; Schöller, Julia; Steinmann, Ulrike; Borkowski, Julia; Findeisen, Peter; Dörries, Rüdiger; Schwerk, Christian; Schroten, Horst; Tenenbaum, Tobias (Virus research, 2012)
Enterovirus is the most common pathogen causing viral meningitis especially in children. Besides the blood-brain barrier (BBB) the choroid plexus, which forms the blood-cerebrospinal-fluid (CSF) barrier (BCSFB), was shown to be involved in the pathogenesis of enteroviral meningitis. In a human in vitro model of the BCSFB consisting of human choroid plexus papilloma cells (HIBCPP), the permissiveness of plexus epithelial cells for Echovirus 30 (EV30) was analyzed by immunoblotting and quantitative real-time PCR (Q-PCR). HIBCPP could be directly infected by EV30 from the apical as well as from the physiological relevant basolateral side. During an infection period of 5h no alterations of barrier function and cell viability could be observed. Analysis of the cytokine/chemokine-profile following enteroviral infection with a cytometric bead array (CBA) and Q-PCR revealed an enhanced secretion of PanGRO (CXCL1, CXCL2 and CXCL3), IL8 and CCL5. Q-PCR showed a significant upregulation of CXCL1, CXCL2 and CXCL3 in a time dependant manner. However, there was only a minor effect of HIBCPP-infection with EV30 on transepithelial T lymphocyte migration with or without the chemoattractant CXCL12. Moreover, CXCL3 did not significantly enhance T cell migrations. Therefore additional factors must be involved for the in vivo reported enhanced T cell migration into the CNS in the context of enteroviral meningitis. As HIBCPP are permissive for infection with EV30, they constitute a valuable human in vitro model to study viral infection at the BCSFB.
Available online 19 September 2012
Gesehen am 26.06.2016